Intensity and prevalence of ectoparasites in whiteleg shrimp Litopenaeus vannamei and mud crab Scylla serrata harvested from Aceh waters Indonesia - Diky Agung Setiawan; Zainal Abidin Muchlisin; Nur Fadli (Depik, 2024)
Ectoparasite infections are a common problem in small-scale aquaculture, exerting a substantial influence on fishery production. In the context of Indonesia, the two prevalent fishery commodities are whiteleg shrimpLitopenaeus vannameiiand mud crabScylla serrata. These species are extensively cultured within Aceh province, using traditional and semi-intensive aquaculture ponds and there are no reports on ectoparasites in these two species of crustaceans. Therefore, this study aimed to analyze the intensity and prevalence of ectoparasites in mud crab and whiteleg shrimp from Aceh between August to December 2022. Mud crab samples were collected from three locations, namely Langsa City, East Aceh, and North Aceh districts, while whiteleg shrimp samples were sampled from coastal ponds in Banda Aceh, Aceh Besar, and Aceh Jaya districts. The samples were collected over five months, and a total of 300 for each species were examined microscopically by scraping the swimming legs body, and gills. Furthermore, macroscopic-sized and microscopic-sized ectoparasites were observed using stereo and binocular microscopes, respectively. The results showed that five species of ectoparasites were recorded during the study, namely Octolasmis sp., Vorticella sp., Epistylis sp., Oodinium sp., and Zoothamnium sp. Mud crab exhibited infestations of Octolasmis sp., Vorticella sp., Epistylis sp., and Oodinium sp., while whiteleg shrimp were infested byVorticellasp.,Epistylissp., andOodiniumsp. In this study, the highest intensity for crab and shrimp was recorded inOctolasmissp. and Epistylissp., in November and September, respectively. The gills showed higher intensity compared to other infested organs and based on sample origin, crab and shrimp from Langsa and Banda Aceh Cities had higher results compared to other locations.The prevalence of ectoparasites exhibited a high value, reaching 100%, showing that crustacean samples were infested by ectoparasites. Therefore, the intensity of ectoparasite was varied according to sample of origin, time of sampling and infested organs. The samples of both crab and whiteleg shrimp from all locations consistently exhibited ectoparasite infestations throughout the entire study period.Keywords:Octolasmis sp.Vorticella sp.Epistylis sp.Oodinium sp.Zoothamnium sp.